Relationship between Organizational Environment & Organizational Commitment: A Case Study of Medical Colleges in Peshawar - Takrim, Kausar; ur Rehman, Atiq; Amin, Suleman (The Journal of Humanities & Social Sciences, 2023)
The purpose of the study is to determine the relationship of organizational environment with the three dimensions of organizational commitment (affective, continuance and normative organizational commitment) among faculty members of public/private medical colleges in Pakistan. A random sample (N=71) is comprised of full time faculty members of one public sector and two private sector medical colleges operating in Peshawar (Pakistan). Following Allen and Meyer’s (1990) approach to OC, data was gathered through questionnaire as the survey instruments. Pearson correlation was computed to analyze the relationships of organizational environment and the sub scales of organizational commitment. The results of this study show statistically positive relationship between organizational environment and all the three dimensions of organizational commitment, and that the majority of faculty members are experiencing greater organizational commitment (affective, continuance, and normative) in the presence of a healthy and positive organizational environment. These findings have implications for recruitment of new faculty members and retention of old ones. Therefore, this study provides empirical data to support theoretical models that focus on organizational environment as antecedents to organizational commitment. Efforts should be made by college deans/principals and faculty members in developing a progressive organizational culture to enhance the organizational commitment of its members.